The first Japanese report on neuromyelitis optica rediscovered: acute bilateral blindness, tetraparesis and respiratory insufficiency in a 35-year-old man (1891) - Jarius, Sven; Wuthenow, Asa-Bettina; Wildemann, Brigitte (Journal of the neurological sciences, 2018)
The term ‘neuromyelitis optica’ (NMO, Devic syndrome) is used to refer to a syndrome characterized by optic neuritis and myelitis. For many decades NMO was classified as a clinical variant of multiple sclerosis (MS). Recent research has shown, however, that NMO differs from MS in terms of immunopathogenesis, clinical presentation, and optimum treatment. In most cases, NMO is caused by autoantibodies to aquaporin-4 or myelin oligodendrocyte glycoprotein. While the history of classic MS has been studied extensively, only relatively little is known about the early history of NMO. Although NMO is considered to be much more prevalent among Asian than among European patients with CNS demyelination, all early reports of NMO reviewed by Eugène Devic and Fernand Gault in their seminal 1894 review and all other reports from the 19th century re-discovered by us over the past years related cases of NMO in patients of European descent. Here, we would like to draw the attention to an early report on NMO in a Japanese patient, published by Tanemichi Aoyama (1859-1917), one of the most eminent physicians of the Meiji period, an era characterized by a Western-style revolution in Japanese medicine. The report was published in 1891, i.e. 3years before Devic and Gault's disease defining study on NMO. To the best of our knowledge, this is the earliest report on an Asian patient with NMO. We give an English translation of the original Japanese report written in bungo (pre-modern Japanese) and discuss the case both in the light of current knowledge on NMO and from a historical perspective.